PENGEMBANGAN MEDIA PUZZLE RUMAH ADAT JOGLO BERBASIS PBL PADA PEMBELAJARAN GEOMETRI MATEMATIKA KELAS V SDN 1 KALORAN TEMANGGUNG - Edy Wasono; Miluwati, Miluwati; Moh Rusnoto Susanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Culture and mathematics are closely related. Ethnomathematics is the study of how mathematics is used and understood in various cultures. This study aims to develop a PBL-based traditional Joglo house puzzle media in mathematics learning in grade V of elementary school. This study uses a modification of the ADDIE development model which uses three stages, namely: 1) Analysis, 2) Design and 3) Development. This stage was modified into three stages because the researcher only wanted to focus on product development planning in order to produce a feasible product. Data collection in this study used the interview stage and distributed questionnaires. Based on the analysis of data obtained through the validation process from several reviewers, namely two media experts and teacher responses. The results of the validation test obtained from media expert I got a score of 3.81 with the Good category, then from media expert II got a score of 4.54 with the Very Good category and the last from the teacher's response got a score of 4.6 with the Very Good category. In accordance with the three values ​​obtained, the average result obtained was 4.31 with the Very Good category. Therefore, based on the values ​​obtained from the validation results, it can be concluded that the development of PBL-based Joglo traditional house puzzle media in geometry learning for grade V of elementary school is feasible to use.